Maslahah Dalam Pertimbangan Hukum Hakim Pada Putusan Izin Poligami Nomor 0020/Pdt.G/2017/Pa.Mn - Izzat Abdika Mukalafin (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
Maslahah actions that encourage human goodness or anything beneficial to human beings. This article is in the decision of the Religious Court of Madiun City number 0020/Pdt.G/2017/PA.Mn. The judge only granted the application for permission to have polygamy and rejected the application for separation of joint property; the decision was not granted on the verdict. The method used in this research is a qualitative research method that produces descriptive data analysis. Primary data in the form of the judge's decision of the Religious Court of Madiun City Number 0020/Pdt.G/2017/PA.Mn The secondary source of library materials in the form of books and interviews with judges. The results of this study there are three conclusions, namely 1). That is the decision with case number 0020/Pdt.G/2017/PA.Mn is by the rules of Maslahah Dzaruriyyah because in this matter, to preserve religion, soul, intellect, lineage, and property have been fulfilled. Only one thing has not been fulfilled about the property, so the more significant problem must come first. 2). The maslahah of formal and material written evidence has been met, but in the evidence of common property is not by the law, the judge rejected it, and it is by the maslahah mu'tabaroh supported by syara '. 3). The maslahah in the witness evidence, including the maslahah hajjiyah, is less than maximum, or it is still doubtful that the witness only knows it. Not by the material requirements (Article 171 HIR/308 RBg) to see, hear, and experience for himself. So the judge gave relief to the parties to support the fulfilment of the maintenance of religion, soul, intellect, lineage and property.